(untitled) (Research in Agriculture Livestock and Fisheries, 2026)
Small indigenous fish species (SIS) are vital to Bangladesh’s food and nutritional security, as fish supply nearly 60% of the country’s daily animal protein intake. Although aquaculture now contributes more than half of national fish production, SIS remain crucial for low-income and nutritionally vulnerable populations. Over 150 species inhabit ponds, beels, haors, baors, rice fields, and floodplains. Consumed whole head, bones, and viscera, SIS provides dense nutrition, rich in protein, polyunsaturated fatty acids, calcium, vitamin A, iron, and zinc, which help combat widespread micronutrient deficiencies and malnutrition. Their regular consumption enhances dietary diversity, maternal and child health, and overall community nutrition. Economically, SIS supports millions of rural households through fishing, trading, and post-harvest processing, often involving women, thereby strengthening rural livelihoods. However, SIS resources are under threat from habitat degradation, pollution, overfishing, climate change, and the expansion of intensive aquaculture, all of which have reduced wild populations. Seasonal water fluctuations, poor policy attention, and lack of integration into mainstream aquaculture further limit their potential. To ensure sustainability, efforts are needed to conserve habitats, promote responsible harvesting, and develop breeding and culture technologies suited to smallholder contexts. This narrative review synthesizes existing knowledge on the nutritional and economic importance of SIS in Bangladesh, emphasizing its role as an affordable solution to malnutrition and poverty reduction. It also underscores the urgent need for ecological restoration, institutional reform, and technological innovation to secure these valuable species for future generations. Res. Agric. Livest. Fish Vol. 12, No. 3, December 2025: 575-588